2018
DOI: 10.3389/fmicb.2018.01497
|View full text |Cite
|
Sign up to set email alerts
|

ArsRS-Dependent Regulation of homB Contributes to Helicobacter pylori Biofilm Formation

Abstract: One elusive area in the Helicobacter pylori field is an understanding of why some infections result in gastric cancer, yet others persist asymptomatically for the life-span of the individual. Even before the genomic era, the high level of intraspecies diversity of H. pylori was well recognized and became an intriguing area of investigation with respect to disease progression. Of interest in this regard is the unique repertoire of over 60 outer membrane proteins (OMPs), several of which have been associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 58 publications
3
34
0
Order By: Relevance
“…In contrast, H. pylori strain G27 readily forms biofilms under nutrient poor and nutrient rich conditions such as those used routinely in the laboratory (Hathroubi, Zerebinski et al 2018. H. pylori G27 therefore appears to be a strong biofilm-producing strain, consistent with its previous use as a model for studying H. pylori biofilm formation (Anderson, Huang et al 2015, Gaddy, Radin et al 2015, Servetas, Carpenter et al 2016, Servetas, Doster et al 2018. Because the pathways for biofilm formation had not yet been characterized in H. pylori strain G27, we performed transcriptomic and genomic approaches to unravel genes associated with the biofilm mode of growth in this strong biofilmforming H. pylori, and characterized how biofilm growth affected antibiotic susceptibility.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…In contrast, H. pylori strain G27 readily forms biofilms under nutrient poor and nutrient rich conditions such as those used routinely in the laboratory (Hathroubi, Zerebinski et al 2018. H. pylori G27 therefore appears to be a strong biofilm-producing strain, consistent with its previous use as a model for studying H. pylori biofilm formation (Anderson, Huang et al 2015, Gaddy, Radin et al 2015, Servetas, Carpenter et al 2016, Servetas, Doster et al 2018. Because the pathways for biofilm formation had not yet been characterized in H. pylori strain G27, we performed transcriptomic and genomic approaches to unravel genes associated with the biofilm mode of growth in this strong biofilmforming H. pylori, and characterized how biofilm growth affected antibiotic susceptibility.…”
Section: Introductionsupporting
confidence: 66%
“…Several studies have shown multiple H. pylori strains form biofilms, including strain G27 (Cole, Harwood et al 2004, Williams, McInnis et al 2008, Yonezawa, Osaki et al 2010, Bessa, Grande et al 2013, Anderson, Huang et al 2015, Servetas, Doster et al 2018). However, these multiple strains had not been compared side-by-side.…”
Section: Biofilm Is a Common Trait Among H Pylori And Strain G27 Is mentioning
confidence: 99%
“…RNA quality was examined on a 2% agarose gel. cDNA synthesis and quantitative reverse transcription-PCR (qRT-PCR) were performed as described previously (66). The qRT-PCRs included a 16S rRNA reference gene and the efflux gene(s) of interest (norA, qacA, or qacC).…”
Section: Figmentioning
confidence: 99%
“…The simultaneous deletion of arsS and nikR genes decreases the normal Hp functionality and results in increasing of the coccoid forms and increased biofilm formation (Servetas et al, 2016). This hyper-biofilm forming phenotype of arsS mutants is found to be mediated by an outer membrane protein, homB (Servetas et al, 2018).…”
Section: Genetic Regulatory Pathways Of Hp Biofilm Formationmentioning
confidence: 99%